Independence Number in Path Graphs - Knor, Martin; Niepel, Ľudovít (Computing and Informatics, 2012)
In the paper we present results, which allow us to compute the independence numbers of P_2-path graphs and P_3-path graphs of special graphs. As P_2(G) and P_3(G) are subgraphs of iterated line graphs L^2(G) and L^3(G), respectively, we compare our results with the independence numbers of corresponding iterated line graphs.